Semi Automatic Tobacco Fertilizer Design and Anthropometry - Wiryono, Budy; Muanah, Muanah; Asriani, Noviani (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2025)
The fertilization process which is carried out by lifting the bucket, then the fertilizer solution is distributed to the roots of the plant by bending and then standing again if the availability of water has run out. If this is done continuously, then many workers complain about work risks such as back pain, arm pain, and so on. This study aims to determine the work risk, anthropometry of manual tobacco fertilizing workers, and to design a semi-automatic tobacco fertilizing device. The method used in this study is an experimental method by designing tools and testing the performance of the designed tools. Parameters observed were: level of worker complaints, worker anthropometry, dimensions and components of emitter discharge fertilization equipment and uniformity of water distribution. The results showed that the most common complaints were on body parts such as the waist, arms and shoulders, which ranged from 78% -94%. Anthropometry to design a tobacco fertilizer using the 50th percentile (P50). Measurement points such as standing height 157 cm, shoulder height standing 127 cm, waist standing 91 cm, hand length 70 cm, and hand width 10 cm. The tobacco fertilizer has components such as frames, container jerry cans, wheels, distribution hoses, panel boxes, stick sprayers. The results of testing the water discharge are by doing 4 repetitions with each discharge having 44 ml/second. The uniformity of water distribution from this tool reaches 100%.